Exercise and NO production: relevance and implications in the cardiopulmonary system - Nosarev, Alexei V.; Smagliy, Lyudmila V.; Anfinogenova, Yana; Popov, Sergey V.; Kapilevich, Leonid V. (Frontiers in Cell and Developmental Biology, 2015)
This article reviews the existing knowledge about the effects of physical exercise on nitric oxide (NO) production in the cardiopulmonary system. The authors review the sources of NO in the cardiopulmonary system; involvement of three forms of NO synthases (eNOS, nNOS, and iNOS) in exercise physiology; exercise-induced modulation of NO and/or NOS in physiological and pathophysiological conditions in human subjects and animal models in the absence and presence of pharmacological modulators; and significance of exercise-induced NO production in health and disease. The authors suggest that physical activity significantly improves functioning of the cardiovascular system through an increase in NO bioavailability, potentiation of antioxidant defense, and decrease in the expression of reactive oxygen species-forming enzymes. Regular physical exercises are considered a useful approach to treat cardiovascular diseases. Future studies should focus on detailed identification of (i) the exercise-mediated mechanisms of NO exchange; (ii) optimal exercise approaches to improve cardiovascular function in health and disease; and (iii) physical effort thresholds.